Developing E-Learning Assisted by Padlet on Matrix Learning to Improve Student Learning Outcomes - Purba, Putri Anggraini (Proceeding International Conference on Religion, Science and Education, 2022)
This study aims to develop Padlet-based online learning media on valid, practical and effective matrix materials to improve student learning outcomes during the covid-19 pandemic at SMK Multi Karya Medan. This type of research is research and development with the ADDIE development model (Analysis, Design, Development, Implementation, Evaluation). The analysis stage is student profile analysis, needs analysis, and constraints. The design stage is designing products and devices. The development stage is developing learning products and tools and conducting validation. The implementation stage is applying learning media. The evaluation stage is to test student learning outcomes after using the media. The validity of the Padlet-based online learning media was assessed by one media expert, one design expert and two content experts with an average score of 3.72 media experts ("very valid" category), design experts 3.88 ("very valid" category), and material expert 3.49 ("valid" category). The practicality of learning media is seen from the student response questionnaires and teacher response questionnaire scores, namely 3.68 and 3.81. The effectiveness of learning media is seen based on the percentage of students' learning completeness, which is 87.5% (28 students out of 32 students are in the "completed" category after participating in learning) with an average score of 83.14. Overall, we can conclude that the pallet-based online learning media developed is valid, practical.